Scaling in Polanyi. Reconsidering the Local in the Age of Neoliberalism - Adaman, Fikret (PARTECIPAZIONE E CONFLITTO, 2017)
There is an increasing interest into Karl Polanyi’s framework and method of analysis in under-standing today’s problems of neoliberalism as well as in thinking about their solutions. In The Great Trans-formation, his magnum opus written in 1944, Polanyi took nation-states and to some extent the global monetary system as his units of analysis without focusing on local-level issues (be in the form of reasons of problems, or resistances, or alternative creations). Motivated to shed light on this lack of focus, this paper aims at contributing to the efforts of extending and widening his vision to incorporate different scales (lo-cal-national-global) in today’s world. The paper first acknowledges and highlights the local as a separate unit in contrast to national and global units; then it unpacks the concept of scale, the way in which the lo-cal-national-global dimensions interact with each other, and the importance of scaling up and down in looking at societal issues. Thereafter, it revisits the Polanyian framework and makes an initial foray to dis-cuss the scale issue, with a focus on the local. It then reconsiders Polanyi’s three forms of integration—"exchange", "reciprocity" and "redistribution"—in an attempt to flesh out the discussion, with some refer-ences to current problematic areas. Finally, it comes up with some policy suggestions and further research areas.